1998
DOI: 10.1007/s004420050433
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotope ratio of tree leaves, boles and fine litter in a tropical forest in Rondônia, Brazil

Abstract: Leaves of 208 trees were collected for isotopic analysis together with wood from 36 tree boles and 18 samples of fine litter from a terra-firme forest located at Samuel Ecological Reserve, Rondônia State, in the southwestern Amazon region. The range of δC values in leaves was from -28 to -36‰, with an average (±1 SD) of -32.1 ± 1.5‰, which was more negative than the δC values of bole samples (-28.4 ± 2.0‰) and fine litter (-28.7 ± 2.0‰). These values are within the range found for tropical and subtropical fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
3
15

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 34 publications
10
57
3
15
Order By: Relevance
“…The variation in foliar d 13 C among co-occurring species revealed in the present study is comparable to levels of interspecific within-site variation found in other terra firme forests in the Amazon Basin (e.g., 9 to 12% at four forest sites (see Figure 1 in Ometto et al 2006), 8% at a forest site in southern Amazonia (Martinelli et al 1998)). One of the explanations for large within-site variation in d 13 C is the ''canopy effect'' that causes leaves closer to the forest floor to have more 13 C-depleted d 13 C signatures relative to leaves in the upper canopy.…”
Section: Interspecific Isotopic Variationsupporting
confidence: 86%
See 1 more Smart Citation
“…The variation in foliar d 13 C among co-occurring species revealed in the present study is comparable to levels of interspecific within-site variation found in other terra firme forests in the Amazon Basin (e.g., 9 to 12% at four forest sites (see Figure 1 in Ometto et al 2006), 8% at a forest site in southern Amazonia (Martinelli et al 1998)). One of the explanations for large within-site variation in d 13 C is the ''canopy effect'' that causes leaves closer to the forest floor to have more 13 C-depleted d 13 C signatures relative to leaves in the upper canopy.…”
Section: Interspecific Isotopic Variationsupporting
confidence: 86%
“…Generally, non-photosynthetic tissues in C 3 plants are 13 C-enriched relative to leaves (Cernusak et al 2009). Paired wood and leaf samples of trees in a terra firme forest in the southwestern Amazon revealed variation in d 13 C (range ¼ -0.85 to þ 9%, n ¼ 33 trees; Martinelli et al 1998) larger than that observed in the vá rzea of the Tarapoto Lakes complex. Although the pattern of 13 C enrichment in wood relative to leaves appears to be widespread across diverse taxa and ecosystems, causal mechanisms remain poorly understood (Bowling et al 2008), and a combination of processes likely contribute to this pattern (Cernusak et al 2009).…”
Section: Within-plant Isotopic Variationmentioning
confidence: 80%
“…The water-use ef®ciency of Palaeozoic plants was calculated with the isotopic composition of atmospheric CO 2 used during photosynthesis (d 13 29 . Plant water-use ef®ciency was calculated as p CO2 3 1 2 2 ¢ a= 2 b a=1:6 where a is fractionation associated with diffusion (4.4½), b is fractionation associated with Rubisco (27½) and 1.6 is the ratio of gaseous diffusivities of CO 2 and water vapour in the air 16 .…”
Section: Methodsmentioning
confidence: 99%
“…This included a total of 15 gymnosperm and 23 angiosperm species, although we note that three publications from the Amazon sampled across a large numbers of species (Broadmeadow et al 1992;Martinelli et al 1998;Ometto et al 2002), which we combined for analyses. After separation of all the individual datasets within publications (i.e.…”
Section: Global Patternsmentioning
confidence: 99%